2022
DOI: 10.3389/fpls.2022.848869
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between CitMYB52 and CitbHLH2 Negatively Regulates Citrate Accumulation by Activating CitALMT in Citrus Fruit

Abstract: Citric acid plays significant roles in numerous physiological processes in plants, including carbon metabolism, signal transduction, and tolerance to environmental stress. For fruits, it has a major effect on fruit organoleptic quality by directly influencing consumer taste. Citric acid in citrus is mainly regulated by the balance between synthesis, degradation, and vacuolar storage. The genetic and molecular regulations of citric acid synthesis and degradation have been comprehensively elucidated. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Although several TF families (e.g. WRKY (Ding et al ., 2013 ; Ye et al ., 2017 ), MYB (Hu et al ., 2017 ) and bHLH (Liu, et al ., 2022 )) have been reported to act as transcription activators or repressors of ALMTs , our results reveal a new transcriptional activator of AcALMT1, which adds to the previously known NAC TF regulatory networks.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although several TF families (e.g. WRKY (Ding et al ., 2013 ; Ye et al ., 2017 ), MYB (Hu et al ., 2017 ) and bHLH (Liu, et al ., 2022 )) have been reported to act as transcription activators or repressors of ALMTs , our results reveal a new transcriptional activator of AcALMT1, which adds to the previously known NAC TF regulatory networks.…”
Section: Discussionsupporting
confidence: 65%
“…However, PpALMT9 exhibited highest expression levels in high‐acid peach cultivars which accumulate citrate throughout fruit development (Zheng et al ., 2021 ). Association of ALMT and citrate was also found in citrus fruit (Liu, et al ., 2022 ). Thus, regulation of ALMTs on malate and citrate may be manifested by specific isoforms for different crops.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, two TFs belonging to the DREB sub‐clade, CsERF054 and CsERF061, were found to be induced by LT (Figure 2c; Figure S4b) and to trans‐activate the CsRuby1 promoter by directly binding to the DRE/CRT cis ‐element (Figures 3a,b and 4a), indicating that CsERF054 and CsERF061 might be crucial cold‐responsive upstream regulators of CsRuby1 in Tarocco blood orange. Citrus is a perennial woody plant, and in previous studies, callus, fruits, and seedlings were normally used to verify gene functions (Fang et al., 2023; Hu et al., 2021; Liu et al., 2022; Zhao et al., 2021). However, there is a lack of tools to verify gene functions in citrus; the anthocyanin accumulation occurs in the very late stages of maturity, when the fruits are not suitable for transient transfection; and blood orange itself does not have seeds therefore seedling populations can not be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate is an intermediate in the tricarboxylic acid (TCA) cycle and its concentration in fruit determines acidity. Many reports over the past two decades have revealed that citrate concentration in citrus fruit is influenced by biosynthesis (Schmidtmann et al ., 2014; Verschueren et al ., 2019), catabolism (Sadka et al ., 2000a,b; Hu et al ., 2015; Huang et al ., 2016), and transportation (Huang et al ., 2016; Liu et al ., 2022). In recent years, it has been demonstrated that gene encoding P‐ATPase ( PH genes) is involved in citrate transport and contributes to citrate accumulation in citrus fruits (Aprile et al ., 2011; Shi et al ., 2015; Guo et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%